Myasthenia gravis in a woman with congenital AChR deficiency due to epsilon-subunit mutations. - Croxen, R; Vincent, A; Newsom-Davis, J; Beeson, D (2002)
A reduction in the number of acetylcholine receptors (AChR) on the postsynaptic membrane is characteristic of MG. This may be inherited (AChR deficiency syndrome) or acquired (MG). The authors report two sisters with AChR deficiency caused by heteroallelic mutations in the AChR epsilon-subunit gene. The younger sister developed MG at 34 years. This unusual case raises the possibility that genetic defects of the AChR might be a factor in the etiology of autoimmune MG.